A Study on the Hydrodynamic Excitation Characteristics of Pump and Pipeline Systems Considering the Weakly Compressible Fluid During the Pump Start-Up Condition - Yonggang Lu; Mengjiao Min; Wei Song; Yun Zhao; Zhengwei Wang (Energies)
With increasing global energy transition and environmental awareness, liquefied natural gas (LNG) is rapidly developing as an efficient and clean energy source. LNG pumps are widely used in industrial applications. This study focuses on the LNG pump and pipeline system, and it innovatively establishes a computational model based on weak compressible fluid in order to better reflect the characteristics of pressure pulsation and the flow situation. Through numerical simulations, the flow characteristics of the pump were analyzed. In addition, the flow conditions at the pipe tee were analyzed, and the attenuation patterns of pressure waves at different frequencies within the pipe were also investigated. The internal flow field of the pump was analyzed at three specific time points. The results indicate that, during the initial start-up phase, the internal flow state of the pump is complex, with significant vortices and pressure fluctuations. As the flow rate and rotational speed increase, the flow gradually stabilizes. Moreover, the pressure pulsation coefficient within the pipeline varies significantly with position.